Sorafenib-based combined molecule targeting in treatment of hepatocellular carcinoma - Gao, Jian-Jun (World J Gastroenterol, 2015)
Sorafenib is the only and standard systematic chemotherapy drug for treatment of advanced hepatocellular carcinoma (HCC) at the current stage. Although sorafenib showed survival benefits in large randomized phase III studies, its clinical benefits remain modest and most often consist of temporary tumor stabilization, indicating that more effective first-line treatment regimens or second-line salvage therapies are required. The molecular pathogenesis of HCC is very complex, involving hyperactivated signal transduction pathways such as RAS/RAF/MEK/ERK and PI3K/AKT/mTOR and aberrant expression of molecules such as receptor tyrosine kinases and histone deacetylases. Simultaneous or sequential abrogation of these critical pathways or the functions of these key molecules involved in angiogenesis, proliferation, and apoptosis may yield major improvements in the management of HCC. In this review, we summarize the emerging sorafenib-based combined molecule targeting for HCC treatment and analyze the rationales of these combinations.